Actions of health education carried out by nurses at school: perception of parents (REME-Revista Mineira de Enfermagem, 2012)
The extension project "Seeds of Knowledge" of a Higher Education Institution inserts the nurse in the children school context, developing educational activities in which perceived the weaknesses of parents in relation to these practices in daily life. This qualitative research aimed to analyze the perception of parents on educational activities undertaken by nursing teachers and students of this institution. Held in july 2011, with twelve parents in a public school in Teresina, from whose speeches were semantically categorized and analyzed according to the theoretical framework, demonstrated the value of these activities, since they are informed of the health status of children, and learn about health-promoting actions and the prevention of diseases, developing them at home, thereby reducing financial expenditures with diseases. A creative and special care exercised by the nurse at school results in a professional development and new strategies in working, where the students are prepared for self-care and the adoption of healthy habits.